Let's expand the expression \((2x^2 - x + 3)(x^2 - 6x + 2)\).
-
First, distribute \(2x^2\) across the second polynomial:
- \(2x^2 \cdot x^2 = 2x^4\)
- \(2x^2 \cdot (-6x) = -12x^3\)
- \(2x^2 \cdot 2 = 4x^2\)
-
Next, distribute \(-x\) across the second polynomial:
- \(-x \cdot x^2 = -x^3\)
- \(-x \cdot (-6x) = 6x^2\)
- \(-x \cdot 2 = -2x\)
-
Finally, distribute \(3\) across the second polynomial:
- \(3 \cdot x^2 = 3x^2\)
- \(3 \cdot (-6x) = -18x\)
- \(3 \cdot 2 = 6\)
Now we have: \[ \begin{align*} 2x^4 & + (-12x^3) + (4x^2) \ & + (-x^3) + (6x^2) + (-2x) \ & + (3x^2) + (-18x) + 6 \end{align*} \]
Now let's combine all of the like terms:
- For \(x^4\): \(2x^4\)
- For \(x^3\): \(-12x^3 - x^3 = -13x^3\)
- For \(x^2\): \(4x^2 + 6x^2 + 3x^2 = 13x^2\)
- For \(x\): \(-2x - 18x = -20x\)
- Constant term: \(6\)
So, after combining like terms, we get: \[ 2x^4 - 13x^3 + 13x^2 - 20x + 6 \]
Thus, the final answer in standard form is: \[ \boxed{2x^4 - 13x^3 + 13x^2 - 20x + 6} \]